Syi’ah dan Al-Azhar: Dampak Ideologis terhadap Perkembangan Pendidikan Islam di Universitas Al-Azhar - Suntiah, Ratu; Zain, Irfan Ahmad; Nurhamzah, Nurhamzah; Muttaqin, Via Putrimawati; Koswara, Ujang (Jurnal Pendidikan Agama Islam Al-Thariqah, 2025)
The aim of this research is to comprehensively reveal the historical picture of the Shia during the Fathimiyyah dynasty and its continuity in influencing the pattern of Islamic education at Al-Azhar University in Cairo at that time. This research was conducted in descriptive qualitative form using the library study method, with data analysis sourced from existing texts or manuscripts, the data used was ready to use without going directly into the field, data collection in the research was carried out by reviewing and/or exploring several journals, books , and documents. The results of this research found that the Shia who developed during the Fathimiyyah period, especially during the development of civilization at Al-Azhar University, were Ismailiyyah Shia, where the Shia believed in twelve Imams, who did not deviate at all or even destroy the Islamic ideology that should be implemented. The influence on Al-Azhar University is of course very large, because the intellectual figures who fill the sections at AL-Azhar University have Shia Ismailiyah backgrounds so the impact of their thought and practice backgrounds refers to the seven pillars, namely: 1) Faith, 2) Taharah; 3) Prayer; 4) Zakat; 5) Shaum; 6) Hajj, and 7) Jihad. This condition has implications for the steadfastness and good academic culture that is always massive, the initial emergence of educational developments pioneered by Ibn Killis who has an Ismaili Shia ideology